Disposition of betamethasone in parturient women after intramuscular administration. - Petersen, M C (1984)
When betamethasone phosphate equivalent to 8 mg betamethasone was administered intramuscularly in solution (Celestone Injection) to pregnant women, a large proportion of this ester was absorbed unchanged. Bioavailability of betamethasone from the phosphate ester was as high as after intravenous injection. When pregnant patients received the equivalent of either 6 or 12 mg betamethasone in a formulation containing 3.1 mg/ml betamethasone acetate suspended in a solution of 4 mg/ml betamethasone phosphate (Celestone Chronodose), much of the phosphate ester was absorbed intact but betamethasone acetate was not detected in plasma. Availability of betamethasone from Celestone Chronodose was much lower than from Celestone Injection. After administration of either formulation, maternal plasma cortisol concentrations fell towards a basal level but were rising again within 2 to 3 days of the last dose. We conclude that Celestone Chronodose does not provide prolonged release of betamethasone and offers no advantage over Celestone Injection.